2022
DOI: 10.1097/j.pain.0000000000002596
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine 16:0 mediates chronic joint pain associated to rheumatic diseases through acid-sensing ion channel 3

Abstract: Supplemental Digital Content is Available in the Text.A combination of clinical and preclinical data that support a role for the lysolipid LPC16:0 via acid-sensing ion channels 3 in chronic joint pain related to rheumatic diseases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…LPC activates ASIC3 channels at pH 7.4 and potentiates its acid‐induced activity (Marra et al, 2016). Recently, the same research group has reported a role for LPC16:0 via ASIC3 channels in chronic pain arising from joints (Jacquot et al, 2022). However, we observed that no detectable current was recorded following application of LPA (range from 0.1 to 10 μM) at physiological pH 7.4, suggesting no activation of any ion channels including ASICs.…”
Section: Discussionmentioning
confidence: 99%
“…LPC activates ASIC3 channels at pH 7.4 and potentiates its acid‐induced activity (Marra et al, 2016). Recently, the same research group has reported a role for LPC16:0 via ASIC3 channels in chronic pain arising from joints (Jacquot et al, 2022). However, we observed that no detectable current was recorded following application of LPA (range from 0.1 to 10 μM) at physiological pH 7.4, suggesting no activation of any ion channels including ASICs.…”
Section: Discussionmentioning
confidence: 99%
“…They are activated by a fast-extracellular acidosis from conditioning physiological pH to acidic test pH and inactivated by sustained extracellular acidosis. Interestingly, rat and human ASIC3 channels can be also activated at neutral (7.4) pH by lipids (arachidonic acid and lysophosphatidylcholine) [ 20 , 21 ] and hASIC3a channels have been shown to be sensitive to both acidic and alkaline pH [ 22 ].…”
Section: Molecular and Functional Properties Of Asicsmentioning
confidence: 99%
“…Regarding joint pain , ASIC3 was found to be expressed in more than 30% of DRG neurons innervating the knee joint in mice [ 227 ], and ASIC expression in DRG is increased in mice models of acute arthritis or rheumatoid arthritis [ 227 , 228 ]. LPC and arachidonic acid (AA) were shown to induce a slow constitutive activation of ASIC3 including the human isoform [ 21 ], and high levels of lysophosphatidylcholine (LPC) were measured in synovial fluids of two independent cohorts of patients with rheumatic diseases, correlated with pain outcomes in the cohort of osteaoarthritis (OA) patients [ 20 ]. LPC also evokes a robust depolarizing current in DRG neurons at physiological pH 7.4, increases the firing of spinal nociceptive neuron innervated by nociceptive C-fiber, and induces pain behavior in rats and mice after subcutaneous co-injection with arachidonic acid, effects that are significantly reduced by ASIC3 blockers, including APETx2, or in ASIC3 knockout mice [ 20 , 21 , 229 ].…”
Section: Pathophysiological Relevance Of Asics and In Vivo Effects Of...mentioning
confidence: 99%
See 2 more Smart Citations